2017
DOI: 10.1039/c7cc06125k
|View full text |Cite
|
Sign up to set email alerts
|

Unique structural micro-adjustments in a new benzothiadiazole-derived Zn(ii) metal organic framework via simple photochemical decarboxylation

Abstract: The first example of micro-adjustments of a metal organic framework (MOF) structure was observed in a new Zn(ii) MOF (Zn-BTDC-M1) derived from a benzothiadiazole-4,7-dicarboxylic acid (HBTDC) ligand using a light-driven decarboxylation process. Interestingly, such decarboxylation occurs at the non-chelated wing of the ligand, which induced a change in the capability of the MOF for physical N adsorption and chemical NH gas adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 52 publications
2
24
1
Order By: Relevance
“…23 Though numerous reports are available where PXRD was used to report the water and thermal stability, studies dealing with photostability have reserved contradictory opinions. 7 Studies dealing with the irradiation of MOFs under UV/visible irradiation have reported signicant alterations in the PXRD pattern, 24,25 while in other published works, PXRD patterns have no major changes. 7,26,27 Thus, the formation of structural defects in a MOF aer irradiation may or may not be traced in the PXRD pattern.…”
Section: Introductionmentioning
confidence: 97%
“…23 Though numerous reports are available where PXRD was used to report the water and thermal stability, studies dealing with photostability have reserved contradictory opinions. 7 Studies dealing with the irradiation of MOFs under UV/visible irradiation have reported signicant alterations in the PXRD pattern, 24,25 while in other published works, PXRD patterns have no major changes. 7,26,27 Thus, the formation of structural defects in a MOF aer irradiation may or may not be traced in the PXRD pattern.…”
Section: Introductionmentioning
confidence: 97%
“…2,1,3-Benzothiadiazole (BTD)i so ne of the most important nuclei in heteroaromatic chemistry,b ecause of its convenient synthesis and attractivep otential applicationsi nd ifferent areas. [1][2][3][4][5][6][7][8][9][10][11] Because of the favorable chemical stabilityo ft his compound, [12] only af ew reports (Scheme 1A)h ave suggested that a1 ,2-benzenediamine compound could be obtainedb y reductives ulfur extrusion from BTD and subsequently transformed into synthetically useful quinoxaline [13][14][15][16] and benzimidazole (BID) [17,18] derivatives, whicha re hard to obtain by traditional direct cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…While complexes that release metal ions in response to light are relatively common, including photocaged complexes that release zinc upon decarboxylation, the analogous photochemistry has not been explored extensively in MOFs. Photodecarboxylation in a benzothiadiazole‐derived MOF led to detectable structural changes and differences in gas adsorption although the experimental data for the proposed behavior was not definitive, and an azobenzene‐containing MOF reportedly degrades upon irradiation; however, irradiation only accelerates the basal rate of decomposition. Local and dynamic structural modulation upon irradiation has been reported with MOFs and covalent organic frameworks (COFs) containing photoswitchable struts; however, direct evidence for the changes are limited.…”
Section: Introductionmentioning
confidence: 99%